Distance Education in India-The State of Art - Ratnalikar, N. V. (Journal of Engineering Education Transformations, 1995)
The Distance Education in India is undergoing change - "From Correspondence Course, Distance Education, Open University, Open School, Networked Educational System ". Distance Education has come to stay on the global plane as well as on the national. The Third Annual Conference on Distance Education was organized by IDEA - The Indian Distance Education Association - at Madras on 12,h & 13'h October 1995. About 200 delegates attended the conference and 70 papers were presented and discussed. The Conference was inaugurated by Prof. Ponnuswamy, Minister of Education, Government of Tamilnadu; The Key note address was delivered by Dr. V. C. Kulandaiswamy, Ex. Vice Chancellor, "Indira Gandhi National Open University, New Delhi" (IGNOU) and the Valedictory address was given by Dr. R. G. Takwale, the present Vice Chancellor of IGNOU. The Key note address and the Valedictory address present the State of the Art of Distance Education in India. Hence, relevant portions from these addresses are presented herewith.